Potential Drug Interactions With Antibiotics On Intensive Care Units: A Retrospective Cross-Sectional Study - Tuba Sena Karacesme; Tuba Kuruoglu; Fatih Temocin (Journal of Global Antimicrobial Resistance)
AIM: This study aims to investigate antibiotic-related potential drug-drug interactions (pDDI) in the treatment regimens of intensive care unit (ICU) patients. BACKGROUND: Antibiotics are extensively utilized pharmaceuticals in ICU. Patients have an elevated risk of pDDIs due to the prevalence of polypharmacy and the complexity of regimens. These interactions may potentially lead to treatment failure or morbidities associated with pDDIs. METHODS: This retrospective cross-sectional study examined the regimens of 263 patients hospitalized in ICUs between June and July 2024. The drug regimens of the first day and any subsequent antibiotic revision days were analyzed. pDDIs were assessed on a five-level scale (UpToDate® DDI checker). RESULTS: We analyzed 300 regimens of 263 patients. A total of 34 different antibiotics were used. pDDIs were observed at various levels in 92(30.6%) of the regimens. The most commonly interacted antibiotic was levofloxacin(n=47). Although teicoplanin was used in 74 regimens, no drug interactions were detected. The only drug that interacted with meropenem was valproic acid. The most common interaction was observed with furosemide, all at level C. There were 20 interactions categorized as level-X, with 18 being antibiotic-antibiotic interactions. CONCLUSION: We found that 30.6% of regimens involving antibiotics exhibited pDDIs. In the studies by Kuscu, and Mehralian, the rates for overall pDDIs found were 53.6% and 60%, while 26% and 87% of these involved antibiotics, respectively. This demonstrates the necessity for careful examination of pDDI when initiating antibiotics in the ICU. Additional research is required to investigate the clinical impacts of these pDDIs involving antibiotics.